Porous body, porous current collector, and solid oxide fuel cell having same
By designing porous bodies with specific hierarchical structures and cobalt content distribution and preparing porous current collectors, the problem of unit rupture for fuel cells caused by the difference in conductivity and thermal expansion coefficients of porous current collectors in solid oxide fuel cells is solved, and efficient conductivity and stable fuel cell performance are achieved.
Patent Information
- Application Number
- CN202380059637.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-28
- Filing Date
- 2023-06-22
- Publication Date
- 2025-03-28
AI Technical Summary
In solid-state oxide fuel cells, the difference between the thermal expansion coefficient of the porous current collector and the thermal expansion coefficient of the fuel cell unit causes the unit for the fuel cell to easily rupture, and at the same time, the electrical conductivity of the porous current collector is excellent but difficult to take into account.
A porous body is designed, and its skeleton is composed of two layers: the outer layer contains more than 50% cobalt and the inner layer contains less than 50%, and is prepared by specific electroplating and heat treatment steps to form a porous current collector with a three-dimensional network structure.
In solid-state oxide fuel cells, the crack suppression of the fuel cell unit and the excellent conductivity of the porous current collector are achieved, and the output performance and stability of the fuel cell are improved.
Smart Images

Figure CN119731811A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a porous body, a porous current collector, and a solid oxide fuel cell having the same. This application claims priority to Japanese patent application No. 2022-155330 filed on September 28, 2022. All the contents described in the Japanese patent application are incorporated into this specification by reference. Background Art
[0002] Conventionally, porous bodies containing nickel and cobalt and porous current collectors produced using the porous bodies have been used in solid oxide fuel cells (Patent Document 1).
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent Application Publication No. 2017-507452. Summary of the invention
[0006] A porous body according to one embodiment of the present invention has a first skeleton having a three-dimensional network structure.
[0007] The first frame is composed of a frame body and a hollow interior surrounded by the frame body.
[0008] The skeleton body is composed of a first layer and a second layer.
[0009] The first layer is located on the outer surface side of the skeleton body,
[0010] The second layer is located on the inner side of the skeleton body,
[0011] The skeleton body contains nickel and cobalt in total of 70 mass % or more,
[0012] The cobalt content in the first layer is 50 mass % or more.
[0013] The cobalt content in the second layer is less than 50% by mass.
[0014] The ratio of the thickness of the first layer to the thickness of the skeleton body is 10% or more and 90% or less. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 This is a schematic partial cross-sectional view schematically showing a partial cross-section of a porous body according to one embodiment of the present invention.
[0016] Figure 2 yes Figure 1 Cross-sectional view along line II-II.
[0017] Figure 3This is a schematic partial cross-sectional view schematically showing a partial cross-section of a porous current collector according to one embodiment of the present invention.
[0018] Figure 4 yes Figure 3 Cross-sectional view along line IV-IV.
[0019] Figure 5 This is a schematic cross-sectional view showing an example of a solid oxide fuel cell according to an embodiment.
[0020] Figure 6 is a schematic cross-sectional view showing another example of a solid oxide fuel cell according to an embodiment.
[0021] Figure 7 It is a schematic diagram showing a method of measuring the value of area resistivity. DETAILED DESCRIPTION
[0022] [Problems to be Solved by the Invention]
[0023] When a porous body containing nickel and cobalt is used in a solid oxide fuel cell, as it is used, the oxidation of the porous body will advance to form a porous current collector containing an oxide with a spinel structure. The oxide with a spinel structure gives the porous current collector excellent electrical conductivity (conductivity). On the other hand, the thermal expansion coefficient of the oxide with a spinel structure has a tendency higher than the thermal expansion coefficient of the fuel cell unit in the solid oxide fuel cell. Therefore, in a solid oxide fuel cell, sometimes a difference in thermal expansion coefficient is generated between a porous current collector and a fuel cell unit in contact with the porous current collector, causing the fuel cell unit to rupture. Therefore, in a solid oxide fuel cell, it is required to take into account both the suppression of the rupture of the fuel cell unit and the excellent conductivity of the porous current collector.
[0024] Therefore, an object of the present invention is to provide a porous body, a porous current collector, and a solid oxide fuel cell having the same, which can achieve both suppression of cracking of a fuel cell unit and excellent conductivity of a porous current collector in a solid oxide fuel cell.
[0025] [Effects of the Invention]
[0026] According to the present invention, it is possible to provide a porous body, a porous current collector, and a solid oxide fuel cell having the same, which can achieve both suppression of cracking of a fuel cell unit and excellent electrical conductivity of a porous current collector in a solid oxide fuel cell.
[0027] [Description of Embodiments of the Invention]
[0028] First, embodiments of the present invention will be listed and described.
[0029] [1] A porous body according to one embodiment of the present invention comprises a first skeleton having a three-dimensional network structure,
[0030] The first frame is composed of a frame body and a hollow interior surrounded by the frame body.
[0031] The above-mentioned skeleton body is composed of a first layer and a second layer.
[0032] The first layer is located on the outer surface side of the skeleton body.
[0033] The second layer is located on the inner side of the frame body.
[0034] The skeleton body contains nickel and cobalt in total of 70 mass % or more,
[0035] The cobalt content in the first layer is 50 mass % or more,
[0036] The cobalt content in the second layer is less than 50% by mass.
[0037] A ratio of the thickness of the first layer to the thickness of the skeleton body is 10% or more and 90% or less.
[0038] The porous body according to one embodiment of the present invention can achieve both suppression of cracking of a fuel cell cell and excellent electrical conductivity of a porous current collector in a solid oxide fuel cell.
[0039] [2] A solid oxide fuel cell according to one embodiment of the present invention comprises the porous body described in [1] above. Thus, the solid oxide fuel cell is less likely to have cracks in the fuel cell unit and has excellent output performance.
[0040] [3] A porous current collector according to one embodiment of the present invention comprises a second skeleton having a three-dimensional network structure.
[0041] The second frame is composed of a frame body and a hollow interior surrounded by the frame body.
[0042] The skeleton body is composed of a first region and a second region.
[0043] The first region is located on the outer surface side of the skeleton body.
[0044] The second region is located on the inner side of the frame body.
[0045] The skeleton body contains nickel, cobalt and oxygen in total of 90 mass % or more,
[0046] The first region has a spinel structure of 80% by volume or more,
[0047] The second region has a layered rock salt structure of 80% or more by volume,
[0048] A ratio of the thickness of the first region to the thickness of the skeleton body is 10% or more and 90% or less.
[0049] The porous current collector according to one embodiment of the present invention can achieve both suppression of cracking of a fuel cell cell and excellent electrical conductivity of the porous current collector in a solid oxide fuel cell.
[0050] [4] In the above [3], it is preferred that the cobalt content in the first region is 50 mass % or more,
[0051] The cobalt content in the second region is less than 50% by mass. Thus, in the solid oxide fuel cell, cracking of the fuel cell unit can be further suppressed, and the porous current collector has a more excellent electrical conductivity.
[0052] [5] A solid oxide fuel cell according to one embodiment of the present invention comprises the porous current collector according to [3] or [4] above. Thus, the solid oxide fuel cell is less likely to have cracks in the fuel cell unit and has excellent output performance.
[0053] [Details of the embodiments of the present invention]
[0054] Below, while referring to the attached Figure 1 A specific example of a porous body, a porous current collector, and a solid oxide fuel cell having the same according to an embodiment of the present invention (hereinafter also referred to as "the present embodiment") is described. In the drawings of the present invention, the same reference numerals represent the same or equivalent parts. In addition, the dimensional relationship of length, width, thickness, depth, etc. may be appropriately changed for the clarity and simplicity of the drawings, and does not necessarily represent the actual dimensional relationship.
[0055] In this specification, expressions in the form of “A to B” refer to the upper and lower limits of a range (i.e., greater than A and less than B). When A has no unit but only B has a unit, the unit of A is the same as that of B.
[0056] In the present specification, when a compound or the like is represented by a chemical formula, unless the atomic ratio is particularly limited, all conventionally known atomic ratios are included, and the atomic ratio is not necessarily limited to the stoichiometric range.
[0057] [Embodiment 1: Porous body]
[0058] use Figure 1 and Figure 2 A porous body 10 according to one embodiment of the present invention will be described.
[0059] A porous body 10 according to one embodiment of the present invention (hereinafter also referred to as "this embodiment") includes a first skeleton 11 having a three-dimensional network structure.
[0060] The first frame 11 is composed of a frame body 15 and a hollow interior 13 surrounded by the frame body 15.
[0061] The skeleton body 15 is composed of a first layer 12 and a second layer 16.
[0062] The first layer 12 is located on the outer surface side of the skeleton body 15.
[0063] The second layer 16 is located on the inner side 13 of the skeleton body 15.
[0064] The skeleton body 15 contains nickel and cobalt in total of 70 mass % or more.
[0065] The cobalt content in the first layer 12 is 50 mass % or more.
[0066] The cobalt content in the second layer 16 is less than 50% by mass.
[0067] The ratio of the thickness of the first layer 12 to the thickness of the skeleton body 15 is 10% or more and 90% or less.
[0068] The porous body 10 of the present invention can achieve both suppression of cracking of the fuel cell unit 100 and excellent electrical conductivity of the porous current collector 20 in a solid oxide fuel cell. The reason for this is presumably as follows.
[0069] (a1) In the porous body 10 of the present invention, there is a first skeleton 11, the first skeleton 11 has a three-dimensional network structure, the first skeleton 11 is composed of a skeleton body 15 and a hollow interior 13 surrounded by the skeleton body 15, the skeleton body 15 is composed of a first layer 12 and a second layer 16, the first layer 12 is located on the outer surface side of the skeleton body 15, the second layer 16 is located on the interior 13 side of the skeleton body 15, the skeleton body 15 contains a total of more than 70% by mass of nickel and cobalt, and the cobalt content in the first layer 12 is more than 50% by mass. When the solid oxide fuel cell 150 having the porous body 10 is operated, the porous body 10 is heated, whereby the nickel and cobalt in the skeleton body 15 react with oxygen in the atmosphere to generate oxides. Here, in the first layer 12 having a relatively high cobalt content, there is a tendency to easily form an oxide having a spinel structure. Therefore, in the porous current collector 20 produced by operating the solid oxide fuel cell 150 having the porous body 10, the skeleton body 25 contains a total of more than 90 mass % of nickel, cobalt and oxygen, and the first region R1 has a spinel structure of more than 80 volume %. That is, the first region R1 contains a large amount of oxides having a spinel structure.
[0070] The oxide having a spinel structure has excellent electrical conductivity. Therefore, in the porous current collector 20, since the first region R1 can richly contain the oxide having a spinel structure, the porous current collector 20 has excellent electrical conductivity.
[0071] (b1) However, the thermal expansion coefficient of the oxide having a spinel structure is higher than the thermal expansion coefficient of the unit for fuel cell. Therefore, in a porous current collector rich in the oxide having a spinel structure, there is usually a difference between the thermal expansion coefficient of the porous current collector and the thermal expansion coefficient of the unit, which leads to a tendency for the unit to easily rupture.
[0072] On the other hand, in the porous body 10 of the present invention, the cobalt content in the second layer 16 is less than 50% by mass. Here, in the second layer 16 having a relatively low cobalt content, there is a tendency to easily form an oxide having a layered rock salt structure as an oxide. Therefore, in the porous current collector 20 produced by operating the solid oxide fuel cell 150 having the porous body 10, the skeleton body 25 contains a total of more than 90% by mass of nickel, cobalt, and oxygen, and the second region R2 can have a layered rock salt structure of more than 80% by volume.
[0073] The thermal expansion coefficient of the oxide having the layered rock salt structure is lower than that of the oxide having the spinel structure, and is close to the thermal expansion coefficient of the fuel cell unit 100. Therefore, since the thermal expansion coefficient of the porous current collector 20 can be suppressed low as a whole, the difference in thermal expansion coefficient with the fuel cell unit 100 can be suppressed. Therefore, in the solid oxide fuel cell, the fuel cell unit 100 can be suppressed from rupturing.
[0074] (c1) Furthermore, in the porous body 10, the skeleton body 15 is composed of the first layer 12 and the second layer 16, and the ratio of the thickness of the first layer 12 to the thickness of the skeleton body 15 is 10% or more and 90% or less. Thus, the porous current collector 20 produced by operating the solid oxide fuel cell 150 having the porous body 10 can have both a first region R1 having a thickness sufficient to improve conductivity and a second region R2 having a thickness sufficient to suppress rupture of the fuel cell unit 100.
[0075] Thus, the porous body 10 of the present embodiment can achieve both suppression of cracking of the fuel cell unit 100 and excellent electrical conductivity of the porous current collector 20 in the solid oxide fuel cell.
[0076] <<First frame>>
[0077] The porous body 10 of the present invention has a first skeleton 11, and the first skeleton 11 has a three-dimensional network structure. "Three-dimensional network structure" refers to a three-dimensional network structure. Figure 1As shown in FIG. 1 , the first skeleton 11 has a three-dimensional network structure, and the three-dimensional network structure has a hole portion 14. The first skeleton 11 is composed of a skeleton body 15 and a hollow interior 13 surrounded by the skeleton body 15. Figure 2 As shown, the first skeleton 11 preferably has a triangular shape in a cross section perpendicular to its length direction. However, the cross-sectional shape of the first skeleton 11 is not limited thereto. The cross-sectional shape of the first skeleton 11 may also be a polygon other than a triangle, such as a quadrilateral or a hexagon. Furthermore, the cross-sectional shape of the first skeleton 11 may also be a circle. In addition, the skeleton body 15 is composed of a first layer 12 and a second layer 16, wherein the first layer 12 is located on the outer surface side of the skeleton body 15, and the second layer 16 is located on the inner side 13 of the skeleton body 15. Here, the "outer surface" of the skeleton body 15 refers to the Figure 2 A surface of the skeleton body 15 that is located on the side opposite to the surface on the inner side 13 .
[0078] The first skeleton 11 preferably has an inner portion 13 surrounded by the skeleton body 15 and has a hollow cylindrical shape, and a cross section perpendicular to the length direction is a triangle or other polygon, or a circle. Since the first skeleton 11 is cylindrical, it has an inner wall forming the inner side of the tube and an outer wall forming the outer side of the tube in the skeleton body 15. The first skeleton 11 can make the porous body 10 very light by making the inner portion 13 surrounded by the skeleton body 15 hollow.
[0079] <Composition of the main frame>
[0080] The skeleton body 15 contains a total of more than 70 mass % of nickel and cobalt. The skeleton body 15 preferably contains a total of more than 70 mass %, more than 75 mass %, and more than 80 mass % of nickel and cobalt. The skeleton body 15 preferably contains a total of less than 100 mass %, less than 90 mass %, and less than 85 mass % of nickel and cobalt. The skeleton body 15 preferably contains a total of more than 70 mass % and less than 100 mass %, more than 75 mass % and less than 90 mass %, and more than 80 mass % and less than 85 mass % of nickel and cobalt. In addition, the total of the nickel content and the cobalt content in the skeleton body 15 can be calculated by adding the nickel content and the cobalt content obtained by the method described later.
[0081] The skeleton body 15 preferably contains nickel in an amount of 10% by mass or more, 20% by mass or more, or 30% by mass or more. The skeleton body 15 preferably contains nickel in an amount of 80% by mass or less, 70% by mass or less, or 60% by mass or less. The skeleton body 15 preferably contains nickel in an amount of 10% by mass or more and 80% by mass or less, 20% by mass or more and 70% by mass or less, or 30% by mass or more and 60% by mass or less.
[0082] The skeleton body 15 preferably contains 10 mass % or more, 20 mass % or more, 30 mass % or more of cobalt. The skeleton body 15 preferably contains 90 mass % or less, 80 mass % or less, 70 mass % or less of cobalt. The skeleton body 15 preferably contains 10 mass % or more and 90 mass % or less, 20 mass % or more and 80 mass % or less, 30 mass % or more and 70 mass % or less of cobalt.
[0083] The respective contents of nickel and cobalt in the skeleton body 15 can be determined by the following method: for the observation image (electron microscope image) of the cross-section cut perpendicular to the length direction of the skeleton body 15, use an EDX (Energy Dispersive X-ray spectrometry) device attached to a scanning electron microscope (SEM) (for example, SEM part: trade name "SUPRA35VP", manufactured by Carl Zeiss Microscopy, EDX part: trade name "octane super", manufactured by Ametek) to analyze.
[0084] It was confirmed that as long as the measurement is performed by the above method on the same skeleton body 15, there is no deviation in the measurement result even if the measurement area is arbitrarily changed.
[0085] As long as the effect of the porous body 10 of the present invention is not affected, the skeleton body 15 can include other elements as constituent elements. The skeleton body 15 can include, for example, manganese, iron, copper, chromium, sodium, potassium, silicon, carbon, phosphorus, sulfur, boron, chlorine, fluorine, magnesium, aluminum, calcium, zinc, gold, silver, nitrogen, molybdenum, tungsten, titanium, etc. as other elements. For example, in the manufacturing method described later, these components are sometimes included as inevitable impurities that are inevitably mixed in. The content of other elements in the skeleton body 15 is preferably calculated as 5% by mass or less with these elements alone, and preferably calculated as 10% by mass or less with the total of these elements. The content of other elements in the skeleton body 15 can be measured by the same method as the respective content of nickel and cobalt in the skeleton body 15.
[0086] It was confirmed that as long as the measurement is performed by the above method on the same skeleton body 15, there is no deviation in the measurement result even if the measurement area is arbitrarily changed.
[0087] <Mass per unit area of the first skeleton>
[0088] In this embodiment, the total mass per unit area of nickel and cobalt in the first skeleton 11 is preferably 200 g / m 2 Above and 1000g / m 2 The total mass per unit area of nickel and cobalt is more preferably 250 g / m 2Above and 900g / m 2 The total mass per unit area of nickel and cobalt can be appropriately adjusted when the first nickel-cobalt alloy is electroplated on the conductive resin molded body in the second step of the method for producing the porous body 10 .
[0089] When the total mass per unit area of nickel and cobalt is converted into the mass per unit volume of the skeleton (the apparent density of the skeleton), it is as follows. That is, the apparent density of the skeleton is preferably 0.14 g / cm 3 Above and 0.75g / cm 3 Below, more preferably 0.18 g / cm 3 Above and 0.65g / cm 3 Here, "the apparent density of the skeleton" is defined by the following formula.
[0090] Apparent density of skeleton [g / cm 3 ]=M[g] / V[cm 3 ]
[0091] M: mass of the skeleton [g]
[0092] V: Volume of the shape of the skeleton [cm 3 ].
[0093] <Porosity of porous body>
[0094] The porosity of the porous body 10 is preferably 40% or more and 98% or less, more preferably 45% or more and 98% or less, and most preferably 50% or more and 98% or less. By setting the porosity of the porous body 10 to be 40% or more, the porous body 10 can be made very light and the surface area of the porous body 10 can be increased. By setting the porosity of the porous body 10 to be 98% or less, the porous body 10 can have sufficient strength.
[0095] The porosity of the first skeleton 11 is defined by the following formula.
[0096] Porosity [%] = [1-{M / (V×d)}]×100
[0097] M: mass of the skeleton [g]
[0098] V: Volume of the shape of the skeleton [cm 3 ]
[0099] d: Density of the metal constituting the skeleton [g / cm 3 ]
[0100] <Pore diameter of porous body>
[0101] The average pore size of the porous body 10 is preferably 60 μm or more and 3500 μm or less. By making the average pore size of the porous body 10 60 μm or more, the strength of the porous body 10 can be improved. By making the average pore size of the porous body 10 3500 μm or less, the bendability (bending workability) of the porous body 10 can be improved. From these viewpoints, the average pore size of the porous body 10 is more preferably 80 μm or more and 1000 μm or less, and most preferably 100 μm or more and 850 μm or less.
[0102] The average pore size of the porous body 10 can be calculated by the following method. First, the porous body 10 is cut perpendicular to the length direction of the first skeleton 11 to expose the cross section of the skeleton. Select a cut cross section, magnify it by 3000 times and observe it using an electron microscope to obtain an observation image. Prepare observation images of at least 10 fields of view, and calculate the number of pores per 1 inch (25.4mm=25400μm) in each of the 10 fields of view. Furthermore, after taking the average value (nc) of the number of pores in the 10 fields of view, substitute it into the following formula, and use the value thus calculated as the average pore size of the porous body 10.
[0103] Average pore size [μm] = 25400 [μm] / nc
[0104] <Thickness of the frame body>
[0105] In the present embodiment, the thickness of the skeleton body 15 is preferably not less than 10 μm and not more than 50 μm. Here, the "thickness of the skeleton body 15" refers to the average value of the shortest distance from the hollow interface with the interior 13 of the first skeleton 11, i.e., the inner wall, to the outer wall of the outer side of the first skeleton 11. The thickness of the skeleton body 15 can be obtained by observing the cross section of the skeleton with an electron microscope.
[0106] Specifically, the thickness of the skeleton body 15 can be obtained by the following method. First, the porous body 10 is cut in a plane with the length direction of the first skeleton 11 as the normal line to expose the cross section of the skeleton body 15. Select a cut cross section, magnify it by 3000 times and observe it using an electron microscope, thereby obtaining an observation image. Then, in the observation image, the thickness of the skeleton body 15 is measured at 10 positions. Then, the average of the measured values at the 10 positions is calculated. The average of the measured values at the 10 positions is equivalent to the thickness of the skeleton body 15 of the present invention.
[0107] <<First floor>>
[0108] <Composition of the first layer>
[0109] The cobalt content in the first layer 12 is 50% by mass or more. Thus, the first region R1 of the porous current collector 20 can have a spinel structure of 80% by volume or more, so that the first region R1 can have excellent conductivity. The lower limit of the cobalt content in the first layer 12 is preferably 52% by mass or more, 55% by mass or more, and 60% by mass or more. The upper limit of the cobalt content in the first layer 12 is preferably 90% by mass or less, 80% by mass or less, and 75% by mass or less. The cobalt content in the first layer 12 is preferably 50% by mass or more and 90% by mass or less, 55% by mass or more and 80% by mass or less, and 60% by mass or more and 75% by mass or less.
[0110] The lower limit of the nickel content in the first layer 12 is preferably 0% by mass or more, 2% by mass or more, or 5% by mass or more. The upper limit of the nickel content in the first layer 12 is preferably 10% by mass or less, 8% by mass or less, or 7% by mass or less. The nickel content in the first layer 12 is preferably 0% by mass or more and 10% by mass or less, 2% by mass or more and 8% by mass or less, or 5% by mass or more and 7% by mass or less.
[0111] The respective contents of cobalt and nickel in the first layer 12 can be obtained by the following method. That is, the contents can be obtained by analyzing the composition of the outer layer (first layer 12) in the skeleton body 15 using an EDX device attached to a scanning electron microscope (SEM) (e.g., SEM part: trade name "SUPRA35VP", manufactured by Carl Zeiss Microscopy, and EDX part: trade name "octane super", manufactured by AMETEK) for an observation image (electron microscope image) of a cross section cut perpendicular to the length direction of the skeleton body 15.
[0112] It was confirmed that as long as the measurement was performed by the above method on the same first layer 12 , there would be no deviation in the measurement result even if the measurement region was arbitrarily changed.
[0113] The first layer 12 preferably contains a total of more than 70% by mass of nickel and cobalt. The first layer 12 preferably contains a total of more than 70% by mass, more than 75% by mass, and more than 80% by mass of nickel and cobalt. The first layer 12 preferably contains a total of less than 100% by mass, less than 90% by mass, and less than 85% by mass of nickel and cobalt. The first layer 12 preferably contains a total of more than 70% by mass and less than 100% by mass, more than 75% by mass and less than 90% by mass, and more than 80% by mass and less than 85% by mass of nickel and cobalt. In addition, the total of the nickel content and the cobalt content in the first layer 12 can be obtained by adding the nickel content and the cobalt content obtained by the above method.
[0114] The first layer 12 may contain other elements as long as they do not affect the effects of the porous body 10 of the present invention. As other elements, manganese, iron, copper, chromium, sodium, potassium, silicon, carbon, phosphorus, sulfur, boron, chlorine, fluorine, magnesium, aluminum, calcium, zinc, gold, silver, nitrogen, molybdenum, tungsten, titanium, etc. can be cited. The content of other elements in the first layer 12 is preferably 5% by mass or less based on these elements alone, and preferably 10% by mass or less based on the total of these elements. The content of other elements in the first layer 12 can be measured by the same method as the content of each of cobalt and nickel in the first layer 12.
[0115] It was confirmed that as long as the measurement was performed by the above method on the same first layer 12 , there would be no deviation in the measurement result even if the measurement region was arbitrarily changed.
[0116] <Thickness of the first layer>
[0117] The ratio of the thickness of the first layer 12 to the thickness of the skeleton body 15 is 10% or more and 90% or less. Thus, the porous current collector 20 produced by operating the solid oxide fuel cell 150 having the porous body 10 can have a first region R1 having a thickness sufficient to improve conductivity. The lower limit of the ratio of the thickness of the first layer 12 to the thickness of the skeleton body 15 is preferably 10% or more, 20% or more, or 30% or more. The upper limit of the ratio of the thickness of the first layer 12 to the thickness of the skeleton body 15 is preferably 90% or less, 85% or less, or 80% or less. The ratio of the thickness of the first layer 12 to the thickness of the skeleton body 15 is preferably 20% or more and 90% or less, 20% or more and 85% or less, or 30% or more and 80% or less.
[0118] The thickness of the first layer 12 is preferably 1 μm or more and 45 μm or less, 5 μm or more and 40 μm or less, or 10 μm or more and 35 μm or less. Thus, the conductivity of the skeleton body 25 of the porous current collector 20 generated by operating the solid oxide fuel cell 150 having the porous body 10 can be further improved, so the conductivity of the porous current collector 20 can be further improved. In addition, the thickness of the first layer 12 can be adjusted by appropriately changing the current density and time as electrolysis conditions in the third step of the method for manufacturing the porous body 10.
[0119] In the porous body 10, the thickness of the first layer 12 can be determined by the following method: That is, the thickness of the first layer 12 can be determined by observing the cross section of the first skeleton 11 in the thickness direction with an electron microscope and measuring the thickness of the layer (first layer 12) outside the skeleton body 15.
[0120] It was confirmed that as long as the measurement was performed by the above method on the same first layer 12 , there would be no deviation in the measurement result even if the measurement region was arbitrarily changed.
[0121] <<Second floor>>
[0122] <Composition of the second layer>
[0123] The cobalt content in the second layer 16 is less than 50% by mass. As a result, the thermal expansion coefficient of the porous current collector 20 generated by operating the solid oxide fuel cell 150 having the porous body 10 can be suppressed to be low as a whole, so the difference between the thermal expansion coefficient of the porous current collector 20 and the thermal expansion coefficient of the fuel cell unit 100 can be suppressed, so in the solid oxide fuel cell, the fuel cell unit 100 can be suppressed from rupture. The lower limit of the cobalt content in the second layer 16 is preferably 10% by mass or more, 20% by mass or more, and 30% by mass or more. The upper limit of the cobalt content in the second layer 16 is preferably less than 48% by mass, 45% by mass or less, and 40% by mass or less. The cobalt content in the second layer 16 is preferably 10% by mass or more and less than 50% by mass, 20% by mass or more and 45% by mass or less, and 30% by mass or more and 40% by mass or less.
[0124] The lower limit of the nickel content in the second layer 16 is preferably 30% by mass or more, 35% by mass or more, or 40% by mass or more. The upper limit of the nickel content in the second layer 16 is preferably 90% by mass or less, 80% by mass or less, or 70% by mass or less. The nickel content in the second layer 16 is preferably 30% by mass or more and 90% by mass or less, 35% by mass or more and 80% by mass or less, or 40% by mass or more and 70% by mass or less.
[0125] The respective contents of cobalt and nickel in the second layer 16 can be obtained by the following method. That is, the contents can be obtained by analyzing the inner layer (second layer 16) of the skeleton body 15 using an EDX device attached to a scanning electron microscope (SEM) (e.g., SEM part: trade name "SUPRA35VP", manufactured by Carl Zeiss Microscopy, and EDX part: trade name "octane super", manufactured by AMETEK) for an observation image (electron microscope image) of a cross section cut perpendicular to the length direction of the skeleton body 15.
[0126] It was confirmed that as long as the measurement was performed on the same second layer 16 by the above method, there would be no deviation in the measurement result even if the measurement region was arbitrarily changed.
[0127] The second layer 16 preferably contains a total of more than 70% by mass of nickel and cobalt. The second layer 16 preferably contains a total of more than 70% by mass, more than 75% by mass, and more than 80% by mass of nickel and cobalt. The second layer 16 preferably contains a total of less than 100% by mass, less than 90% by mass, and less than 85% by mass of nickel and cobalt. The second layer 16 preferably contains a total of more than 70% by mass and less than 100% by mass, more than 75% by mass and less than 90% by mass, and more than 80% by mass and less than 85% by mass of nickel and cobalt. In addition, the total of the nickel content and the cobalt content in the second layer 16 can be obtained by adding the nickel content and the cobalt content obtained by the above method.
[0128] The second layer 16 may contain other elements as long as they do not affect the effects of the porous body 10 of the present invention. As other elements, manganese, iron, copper, chromium, sodium, potassium, silicon, carbon, phosphorus, sulfur, boron, chlorine, fluorine, magnesium, aluminum, calcium, zinc, gold, silver, nitrogen, molybdenum, tungsten, titanium, etc. can be cited. The content of other elements in the second layer 16 is preferably 5% by mass or less based on these elements alone, and preferably 10% by mass or less based on the total of these elements. The content of other elements in the second layer 16 can be measured by the same method as the content of each of cobalt and nickel in the second layer 16.
[0129] It was confirmed that as long as the measurement was performed on the same second layer 16 by the above method, there would be no deviation in the measurement result even if the measurement region was arbitrarily changed.
[0130] <Thickness of the second layer>
[0131] The ratio of the thickness of the second layer 16 to the thickness of the skeleton body 15 is 10% or more and 90% or less. Thus, the porous current collector 20 produced by operating the solid oxide fuel cell 150 having the porous body 10 can have a second region R2 having a thickness sufficient to suppress the occurrence of ruptures in the fuel cell unit 100. The lower limit of the ratio of the thickness of the second layer 16 to the thickness of the skeleton body 15 is preferably 10% or more, 15% or more, or 25% or more. The upper limit of the ratio of the thickness of the second layer 16 to the thickness of the skeleton body 15 is preferably 90% or less, 80% or less, or 70% or less. The ratio of the thickness of the second layer 16 to the thickness of the skeleton body 15 is preferably 10% or more and 90% or less, 15% or more and 80% or less, or 25% or more and 70% or less.
[0132] The thickness of the second layer 16 is preferably 1 μm or more and 45 μm or less, 3 μm or more and 35 μm or less, or 5 μm or more and 25 μm or less. Thus, the porous current collector 20 produced by operating the solid oxide fuel cell 150 having the porous body 10 can further suppress the occurrence of rupture of the fuel cell unit 100. In addition, the thickness of the second layer 16 can be adjusted by appropriately changing the current density and time as electrolysis conditions in the second step of the method for manufacturing the porous body 10.
[0133] In the porous body 10, the thickness of the second layer 16 can be determined by the following method: That is, the thickness of the first layer 12 can be determined by observing the cross section of the first skeleton 11 in the thickness direction with an electron microscope and measuring the thickness of the layer (second layer 16) inside the skeleton body 15.
[0134] It was confirmed that as long as the measurement was performed on the same second layer 16 by the above method, there would be no deviation in the measurement result even if the measurement region was arbitrarily changed.
[0135] <<Shape of porous body>>
[0136] The porous body 10 of the present embodiment can have various shapes such as sheet, rectangular, spherical, and cylindrical in appearance. The porous body 10 is particularly preferably in the form of a sheet, with a thickness of 0.2 mm or more and 2 mm or less. The thickness of the porous body 10 is more preferably 0.5 mm or more and 1 mm or less. By making the thickness of the porous body 10 less than 2 mm, a porous body 10 thinner than before can be formed, reducing the amount of metal required. By making the thickness of the porous body 10 more than 0.2 mm, it can have the required strength. The thickness of the porous body 10 can be measured, for example, by a commercially available digital thickness gauge (Dele Co., Ltd.).
[0137] <<Method for producing porous body>>
[0138] The porous body 10 of the present embodiment can be manufactured by, for example, the following method. That is, the porous body 10 can be manufactured by the following method for manufacturing the porous body 10, which sequentially includes:
[0139] In a first step, a conductive coating layer containing conductive carbon is formed on a surface of a resin molded body formed of a foamed resin to obtain a conductive resin molded body;
[0140] In the second step, a first nickel-cobalt alloy is electroplated on the conductive resin molded body using an electroplating bath containing less than 20 g / L of cobalt to obtain a first porous body precursor;
[0141] A third step is to perform a second nickel-cobalt alloy electroplating on the first porous body precursor using an electroplating bath containing 90 g / L or more of cobalt to obtain a second porous body precursor; and
[0142] In the fourth step, the second porous body precursor is subjected to a heat treatment in the atmosphere to obtain the porous body 10 .
[0143] <First step>
[0144] First, a resin molded body formed of a foamed resin is prepared. Examples of the foamed resin include polyurethane resins and melamine resins. Commercially available resin molded bodies formed of foamed resins can be used. Next, in order to impart conductivity to the resin molded body, a conductive coating layer is formed on the surface of the resin molded body. The method for forming the conductive coating layer is not particularly limited. Examples include: a method of coating and / or impregnating the surface of the resin molded body with a conductive coating containing conductive particles such as carbon and conductive ceramics and a binder; a method of forming a layer formed of conductive metals such as nickel and copper on the surface of the resin molded body by an electroless plating method; and a method of forming a layer formed of a conductive metal on the surface of the resin molded body by a vapor deposition method or a sputtering method. In this way, a conductive resin molded body can be obtained.
[0145] <Second step>
[0146] Next, the first nickel-cobalt alloy is electroplated on the conductive resin molded body using an electroplating bath with a cobalt content of less than 20 g / L to obtain a first porous body precursor. Thus, the cobalt content in the second layer 16 can be made less than 50% by mass in the porous body 10. In addition, the electroplating method is not particularly limited, and electroless plating can also be applied. From the viewpoint of efficiency, the electroplating method preferably uses electrolytic plating (so-called electroplating). In electrolytic plating, a conductive resin molded body is used as a cathode.
[0147] As the electroplating bath used in the first nickel-cobalt alloy electroplating, a known electroplating bath can be used as long as it contains less than 20 g / L of cobalt. For example, a Watt bath, a chlorinated bath, an aminosulfonic acid bath, etc. can be used. For example, as the bath composition and electrolysis conditions of the first nickel-cobalt alloy electroplating, the following examples can be cited.
[0148] (Bath composition)
[0149] Salt (aqueous solution): Nickel sulfamate (contains 80-150 g / L of nickel in the plating bath)
[0150] Cobalt sulfamate (containing less than 20 g / L of cobalt in the electroplating bath)
[0151] Boric acid: 30-40 g / L
[0152] pH: 4.0~4.5
[0153] (Electrolysis Conditions)
[0154] Temperature: 50~60℃
[0155] Current density: 5~10A / dm 2
[0156] Anode: Insoluble anode
[0157] Time: 3 to 30 minutes
[0158] In this way, a first porous body precursor in which the nickel-cobalt alloy is plated on the conductive resin molded body can be obtained.
[0159] <Third step>
[0160] Next, a second nickel-cobalt alloy is electroplated on the first porous body precursor using a plating bath containing 90 g / L or more cobalt to obtain a second porous current collector precursor. Thus, the cobalt content in the first layer 12 can be made to be 50% by mass or more in the porous body 10. In addition, the electroplating method is not particularly limited, and electroless plating can also be applied. From the viewpoint of efficiency, the electroplating method preferably uses electrolytic plating (so-called electroplating). In electrolytic plating, a conductive resin molded body is used as a cathode.
[0161] As the electroplating bath used in the second nickel-cobalt alloy electroplating, as long as it contains more than 90 g / L of cobalt, a known electroplating bath can be used. For example, a Watt bath, a chlorinated bath, an aminosulfonic acid bath, etc. can be used. For example, as the bath composition and electrolysis conditions of the second nickel-cobalt alloy electroplating, the following examples can be cited.
[0162] (Bath composition)
[0163] Salt (aqueous solution): Nickel sulfamate (contains 80-150 g / L of nickel in the plating bath)
[0164] Cobalt sulfamate (contains more than 90g / L of cobalt in the electroplating bath)
[0165] Boric acid: 30-40 g / L
[0166] pH: 4.0~4.5
[0167] (Electrolysis Conditions)
[0168] Temperature: 50~60℃
[0169] Current density: 5~10A / dm 2
[0170] Anode: Insoluble anode
[0171] Time: 3 to 30 minutes
[0172] In this way, a second porous body precursor in which the nickel-cobalt alloy is plated on the first porous body precursor can be obtained.
[0173] <Fourth step>
[0174] Next, by performing heat treatment on the second porous body precursor in the atmosphere, the porous body 10 is obtained. The conditions of the heat treatment can be set as follows, for example.
[0175] (Heat treatment conditions)
[0176] Temperature: 600~1000℃
[0177] Time: 5-15 minutes
[0178] When the second porous body precursor is heat-treated in the air, the resin component in the conductive resin molded body is burned and removed. Therefore, the portion corresponding to the resin molded body in the second porous body precursor disappears, and the interior 13 of the porous body 10 becomes a hollow region.
[0179] By going through the above steps, the porous body 10 of the present embodiment 1 can be manufactured. That is, the porous body 10 has a first skeleton 11, the first skeleton 11 has a three-dimensional network structure, the first skeleton 11 is composed of a skeleton body 15 and a hollow interior 13 surrounded by the skeleton body 15, the skeleton body 15 is composed of a first layer 12 and a second layer 16, the first layer 12 is located on the outer surface side of the skeleton body 15, the second layer 16 is located on the interior 13 side of the skeleton body 15, the skeleton body 15 contains a total of 70% by mass or more of nickel and cobalt, the cobalt content in the first layer 12 is 50% by mass or more, the cobalt content in the second layer 16 is less than 50% by mass, and the ratio of the thickness of the first layer 12 to the thickness of the skeleton body 15 is 10% or more and 90% or less.
[0180] [Embodiment 2: Solid Oxide Fuel Cell Having a Porous Body]
[0181] use Figure 5 A solid oxide fuel cell according to one embodiment of the present invention will be described. Figure 5 Schematic cross-sectional view showing a solid oxide fuel cell according to one embodiment of the present invention. Figure 5In the embodiment, the solid oxide fuel cell has a porous body 110 for a hydrogen electrode, a porous body 120 for an air electrode, and a unit 100 for a fuel cell. The unit 100 for a fuel cell is arranged between the porous body 110 for a hydrogen electrode and the porous body 120 for an air electrode. Here, the "porous body 110 for a hydrogen electrode" refers to a porous body on the side where hydrogen is supplied in a fuel cell. The "porous body 120 for an air electrode" refers to a porous body on the side where a gas containing oxygen (such as air) is supplied in a fuel cell. In the solid oxide fuel cell of the present embodiment, the porous body 120 for an air electrode includes the porous body 10 of the present embodiment 1. That is, the solid oxide fuel cell of the present embodiment has the porous body 10 of the present embodiment 1. As a result, the rupture of the unit 100 for a fuel cell is not likely to occur, and a solid oxide fuel cell with excellent output performance can be provided.
[0182] The fuel cell unit 100 can have an air electrode, a hydrogen electrode, an electrolyte layer disposed between the air electrode and the hydrogen electrode, and an intermediate layer (not shown) disposed between them to prevent the electrolyte layer and the air electrode from reacting. As the air electrode, for example, an oxide of LaSrCo (LSC) can be used. As the electrolyte layer, for example, an oxide of Zr doped with Y (YSZ) can be used. As the intermediate layer, for example, an oxide of Ce doped with Gd (GDC) can be used. As the hydrogen electrode, for example, a mixture of YSZ and NiO2 can be used.
[0183] exist Figure 5 In the embodiment, the solid oxide fuel cell further comprises: a first connector 112 having a fuel flow channel 114; and a second connector 122 having an oxidant flow channel 124. The fuel flow channel 114 is a flow channel for supplying fuel (e.g., hydrogen) to the hydrogen electrode. The fuel flow channel 114 is disposed on the main surface of the first connector 112 that faces the porous body 110 for the hydrogen electrode. The oxidant flow channel 124 is a flow channel for supplying an oxidant (e.g., oxygen) to the air electrode. The oxidant flow channel 124 is disposed on the main surface of the second connector 122 that faces the porous body 120 for the air electrode.
[0184] <<Method for manufacturing a solid oxide fuel cell having a porous body>>
[0185] The solid oxide fuel cell 150 having the porous body 10 of the present embodiment can be manufactured by appropriately using a known method, except that the porous body 10 of the present embodiment 1 is used in the air electrode porous body 120. Therefore, the method for manufacturing the solid oxide fuel cell 150 having the porous body 10 should not be particularly limited, except that the porous body 10 of the present embodiment 1 is used.
[0186] [Embodiment 3: Porous Current Collector]
[0187] use Figure 3 and Figure 4 The porous current collector 20 according to one embodiment of the present invention will be described.
[0188] The porous current collector 20 according to one embodiment of the present invention (hereinafter also referred to as “this embodiment”) has a second skeleton 21 having a three-dimensional network structure.
[0189] The second frame 21 is composed of a frame body 25 and a hollow interior 23 surrounded by the frame body 25.
[0190] The skeleton body 25 is composed of a first region R1 and a second region R2.
[0191] The first region R1 is located on the outer surface side of the skeleton body 25.
[0192] The second region R2 is located on the inner portion 23 of the skeleton body 25.
[0193] The skeleton body 25 contains nickel, cobalt, and oxygen in total at 90 mass % or more.
[0194] The first region R1 has a spinel structure of 80% by volume or more,
[0195] The second region R2 has a layered rock salt structure of 80% by volume or more.
[0196] The ratio of the thickness of the first region R1 to the thickness of the skeleton body 25 is 10% or more and 90% or less.
[0197] The porous current collector 20 of the present invention can achieve both suppression of cracking of the fuel cell unit 100 and excellent electrical conductivity of the porous current collector 20 in a solid oxide fuel cell. The reason for this is presumably as follows.
[0198] (a2) The porous current collector 20 of the present invention has a second skeleton 21, the second skeleton 21 has a three-dimensional network structure, the second skeleton 21 is composed of a skeleton body 25 and a hollow interior 23 surrounded by the skeleton body 25, the skeleton body 25 is composed of a first region R1 and a second region R2, the first region R1 is located on the outer surface side of the skeleton body 25, the second region R2 is located on the interior 23 side of the skeleton body 25, the skeleton body 25 contains a total of more than 90 mass% of nickel, cobalt and oxygen, and the first region R1 has a spinel structure of more than 80 volume%. Thus, since the first region R1 can contain a rich amount of oxides having a spinel structure, the porous current collector 20 can have excellent conductivity.
[0199] (b2) However, the thermal expansion coefficient of the oxide having a spinel structure is higher than the thermal expansion coefficient of the unit for fuel cell. Therefore, in a porous current collector rich in the oxide having a spinel structure, there is usually a difference between the thermal expansion coefficient of the porous current collector and the thermal expansion coefficient of the unit, which makes the unit prone to rupture.
[0200] On the other hand, in the porous current collector 20 of the present invention, since the second region R2 has a layered rock salt structure of more than 80% by volume, the second region R2 can contain an oxide having a layered rock salt structure in abundance. Here, the thermal expansion coefficient of the oxide having a layered rock salt structure is lower than the thermal expansion coefficient of the oxide having a spinel structure. Therefore, since the thermal expansion coefficient of the porous current collector 20 can be suppressed to be low as a whole, the difference in thermal expansion coefficient with the fuel cell unit 100 can be suppressed. Therefore, in a solid oxide fuel cell, the fuel cell unit 100 can be suppressed from rupture.
[0201] (c2) Furthermore, the skeleton body 25 is composed of the first region R1 and the second region R2, and the ratio of the thickness of the first region R1 to the thickness of the skeleton body 25 is 10% or more and 90% or less. Thus, the porous current collector 20 can have both the first region R1 having a thickness sufficient to improve the conductivity and the second region R2 having a thickness sufficient to suppress the occurrence of rupture of the fuel cell unit 100.
[0202] That is, the porous current collector 20 of the present embodiment can achieve both suppression of cracking of the fuel cell unit 100 and excellent electrical conductivity of the porous current collector 20 in the solid oxide fuel cell.
[0203] <<Second frame>>
[0204] The porous current collector 20 of the present invention has a second skeleton 21, and the second skeleton 21 has a three-dimensional network structure. "Three-dimensional network structure" refers to a three-dimensional network structure. Figure 3 As shown in FIG. 1 , the second skeleton 21 has a three-dimensional network structure having a hole portion 24. The second skeleton 21 is composed of a skeleton body 25 and a hollow interior 23 surrounded by the skeleton body 25. Figure 4 As shown, the second skeleton 21 preferably has a triangular shape in a cross section perpendicular to its length direction. However, the cross-sectional shape of the second skeleton 21 is not limited thereto. The cross-sectional shape of the skeleton 21 may also be a polygon other than a triangle, such as a quadrilateral or a hexagon. Furthermore, the cross-sectional shape of the second skeleton 21 may also be a circle. In addition, the skeleton body 25 is composed of a first region R1 and a second region R2, wherein the first region R1 is located on the outer surface side of the skeleton body 25, and the second region R2 is located on the inner 23 side of the skeleton body 25. Here, the "outer surface" of the skeleton body 25 refers to the Figure 4A surface of the skeleton body 25 that is located on the side opposite to the surface on the inner side 23 .
[0205] That is, the second skeleton 21 preferably has an inner portion 23 surrounded by the skeleton body 25 and has a hollow cylindrical shape, and the cross section orthogonal to the length direction is a triangle or other polygon, or a circle. Since the second skeleton 21 is cylindrical, it has an inner wall forming the inner side of the cylinder and an outer wall forming the outer side of the cylinder in the skeleton body 25. The second skeleton 21 can make the porous current collector 20 very light by making the inner portion 23 surrounded by the skeleton body 25 hollow.
[0206] <Composition of the main frame>
[0207] The skeleton body 25 contains a total of more than 90 mass % of nickel, cobalt and oxygen. The skeleton body 25 preferably contains a total of more than 90 mass %, more than 92 mass %, and more than 95 mass % of nickel, cobalt and oxygen. The skeleton body 25 preferably contains a total of less than 100 mass %, less than 99 mass %, and less than 98 mass % of nickel, cobalt and oxygen. The skeleton body 25 preferably contains a total of more than 90 mass % and less than 100 mass %, more than 92 mass % and less than 99 mass %, and more than 95 mass % and less than 98 mass % of nickel, cobalt and oxygen. In addition, the total of the nickel content, cobalt content and oxygen content in the skeleton body 25 can be obtained by adding the nickel content, cobalt content and oxygen content in the skeleton body 25 obtained by the method described later.
[0208] The skeleton body 25 preferably contains nickel of 10 mass % or more, 20 mass % or more, or 30 mass % or more. The skeleton body 25 preferably contains nickel of 80 mass % or less, 70 mass % or less, or 60 mass % or less. The skeleton body 25 preferably contains nickel of 10 mass % or more and 80 mass % or less, 20 mass % or more and 70 mass % or less, or 30 mass % or more and 60 mass % or less.
[0209] The skeleton body 25 preferably contains 10 mass % or more, 20 mass % or more, 30 mass % or more of cobalt. The skeleton body 25 preferably contains 90 mass % or less, 80 mass % or less, 70 mass % or less of cobalt. The skeleton body 25 preferably contains 10 mass % or more and 90 mass % or less, 20 mass % or more and 80 mass % or less, 30 mass % or more and 70 mass % or less of cobalt.
[0210] The skeleton body 25 preferably contains 10% by mass or more, 20% by mass or more, or 30% by mass or more of oxygen. The skeleton body 25 preferably contains 40% by mass or less, 38% by mass or less, or 36% by mass or less of oxygen. The skeleton body 25 preferably contains 10% by mass or more and 40% by mass or less, 20% by mass or more and 38% by mass or less, or 30% by mass or more and 36% by mass or less of oxygen.
[0211] The respective contents of nickel, cobalt and oxygen in the skeleton body 25 can be determined by the following method: an observation image (electron microscope image) of a cross section of the skeleton cut perpendicular to the length direction of the skeleton body 25 is analyzed using an EDX device attached to a scanning electron microscope (SEM) (for example, SEM part: trade name "SUPRA35VP", manufactured by Carl Zeiss Microscopy, and EDX part: trade name "octane super", manufactured by Ametek).
[0212] It was confirmed that as long as the measurement is performed by the above method on the same skeleton body 25, there is no deviation in the measurement result even if the measurement area is arbitrarily changed.
[0213] As long as the effect of the porous current collector 20 of the present invention is not affected, the skeleton body 25 can include other elements as constituent elements. The skeleton body 25 may include, for example, manganese, iron, copper, chromium, sodium, potassium, silicon, carbon, phosphorus, sulfur, boron, chlorine, fluorine, magnesium, aluminum, calcium, zinc, gold, silver, nitrogen, molybdenum, tungsten, titanium, etc. as other elements. For example, in the manufacturing method described later, these components are sometimes included as inevitable impurities that are inevitably mixed in. The content of other elements in the skeleton body 25 is preferably calculated as 5% by mass or less with these elements alone, and preferably calculated as 10% by mass or less with the total of these elements. The content of other elements in the skeleton body 25 can be measured by the same method as the content of each of nickel, cobalt and oxygen in the skeleton body 25.
[0214] <Mass per unit area of the second skeleton>
[0215] In this embodiment, the second skeleton 21 preferably has a total mass per unit area of nickel and cobalt of 200 g / m 2 Above and 1000g / m 2 The total mass per unit area of nickel and cobalt is more preferably 250 g / m 2 Above and 900g / m 2 The total mass per unit area of nickel and cobalt can be appropriately adjusted when performing the first nickel-cobalt alloy electroplating and the second nickel-cobalt alloy electroplating in the second step and the third step of the method for producing a porous body.
[0216] When the total mass per unit area of nickel and cobalt is converted into the mass per unit volume of the second skeleton 21 (the apparent density of the skeleton), it is as follows. That is, the apparent density of the second skeleton 21 is preferably 0.14 g / cm 3 Above and 0.75g / cm 3 Below, more preferably 0.18 g / cm 3Above and 0.65g / cm 3 Here, "the apparent density of the skeleton" is defined by the following formula.
[0217] Apparent density of skeleton [g / cm 3 ]=M[g] / V[cm 3 ]
[0218] M: mass of the skeleton [g]
[0219] V: Volume of the shape of the skeleton [cm 3 ].
[0220] <Porosity of the porous current collector 20>
[0221] The porosity of the porous current collector 20 is preferably 40% or more and 98% or less, more preferably 45% or more and 98% or less, and most preferably 50% or more and 98% or less. By making the porosity of the porous current collector 20 40% or more, the porous current collector 20 can be made very light and the surface area of the porous current collector 20 can be increased. By making the porosity of the porous current collector 20 98% or less, the porous current collector 20 can have sufficient strength.
[0222] The porosity of the porous current collector 20 is defined by the following formula.
[0223] Porosity [%] = [1-{M / (V×d)}]×100
[0224] M: mass of the skeleton [g]
[0225] V: Volume of the shape of the skeleton [cm 3 ]
[0226] d: Density of the metal constituting the skeleton [g / cm 3 ]
[0227] <Pore diameter of porous current collector>
[0228] The average pore size of the porous current collector 20 is preferably 60 μm or more and 3500 μm or less. By making the average pore size of the porous current collector 20 60 μm or more, the strength of the porous current collector 20 can be improved. By making the average pore size of the porous current collector 20 3500 μm or less, the bendability (bending workability) of the porous current collector 20 can be improved. From these viewpoints, the average pore size of the porous current collector 20 is more preferably 80 μm or more and 1000 μm or less, and most preferably 100 μm or more and 850 μm or less.
[0229] The average pore size of the porous current collector 20 can be calculated by the following method. First, the porous current collector 20 is cut perpendicular to the length direction of the second skeleton 21 to expose the cross section of the second skeleton 21. Select a cut section, magnify it by 3000 times and observe it using an electron microscope to obtain an observation image. Prepare observation images of at least 10 viewing fields, and in each of the 10 viewing fields, calculate the number of pores per 1 inch (25.4mm=25400μm). Furthermore, after taking the average value (nc) of the number of pores in the 10 viewing fields, substitute it into the following formula, and use the calculated value as the average pore size of the porous current collector 20.
[0230] Average pore size [μm] = 25400 [μm] / nc
[0231] <Thickness of the frame body>
[0232] In the present embodiment, the lower limit of the thickness of the skeleton body 25 is preferably 10 μm or more, 13 μm or more, or 15 μm or more. The upper limit of the thickness of the skeleton body 25 is preferably 50 μm or less, 40 μm or less, or 30 μm or less. The thickness of the skeleton body 25 is preferably 10 μm or more and 50 μm or less, 13 μm or more and 40 μm or less, or 15 μm or more and 30 μm or less. Here, the "thickness of the skeleton body 25" refers to the shortest distance from the inner wall of the hollow interior 23 facing the skeleton to the outer wall of the outer side of the skeleton, and the average value thereof is taken as the "thickness of the skeleton body 25". The thickness of the skeleton body 25 can be obtained by observing the cross-section of the second skeleton 21 with an electron microscope.
[0233] Specifically, the thickness of the skeleton body 25 can be calculated by the following method. First, the porous current collector 20 is cut perpendicular to the length direction of the second skeleton 21 to expose the cross section of the skeleton body 25. Select a cut cross section, magnify it by 3000 times and observe it using an electron microscope to obtain an observation image. Then, in the observation image, the shortest distance from the inner wall of the hollow interior 23 facing the second skeleton 21 to the outer wall of the outer side of the second skeleton 21 is measured at 10 positions. Calculate the average of the measured values at the 10 positions. The average of the measured values at the 10 positions is equivalent to the "thickness of the skeleton body 25" of the present invention.
[0234] <First Area>
[0235] (Crystal Structure)
[0236] The first region R1 has a spinel structure of more than 80% by volume. Thus, a large amount of oxides having a spinel structure can be contained in the first region R1, so the porous current collector 20 can have excellent conductivity. The first region R1 preferably has a spinel structure of more than 80% by volume, more than 85% by volume, and more than 90% by volume. The first region R1 preferably has a spinel structure of less than 100% by volume, less than 98% by volume, and less than 96% by volume. The first region R1 preferably has a spinel structure of more than 80% by volume and less than 100% by volume, more than 85% by volume and less than 98% by volume, and more than 90% by volume and less than 96% by volume.
[0237] (thickness)
[0238] The ratio of the thickness of the first region R1 to the thickness of the skeleton body 25 is 10% or more and 90% or less. Thus, the conductivity of the skeleton body 25 can be improved, and thus the conductivity of the porous current collector 20 can be improved. The lower limit of the ratio of the thickness of the first region R1 to the thickness of the skeleton body 25 is preferably 10% or more, 20% or more, or 30% or more. The upper limit of the ratio of the thickness of the first region R1 to the thickness of the skeleton body 25 is preferably 90% or less, 85% or less, or 80% or less. The ratio of the thickness of the first region R1 to the thickness of the skeleton body 25 is preferably 10% or more and 90% or less, 20% or more and 85% or less, or 30% or more and 80% or less. The ratio of the thickness of the first region R1 to the thickness of the skeleton body 25 is calculated as a percentage of the value obtained by dividing the thickness of the first region R1 by the thickness of the skeleton body 25.
[0239] The thickness of the first region R1 is preferably 1 μm to 45 μm, 5 μm to 40 μm, or 10 μm to 35 μm. This can further improve the conductivity of the skeleton body 25, thereby further improving the conductivity of the porous current collector 20. In addition, the thickness of the first region R1 can be adjusted by appropriately changing the current density and time as electrolysis conditions in the third step of the method for manufacturing the porous body.
[0240] In the porous current collector 20, the thickness of the first region R1 can be obtained by observing the cross section of the skeleton with a scanning electron microscope and measuring the region (first region R1) on the outer surface side of the skeleton body 25. It was confirmed that as long as the measurement is performed by the above method in the same porous current collector 20, there is no deviation in the measurement result even if the measurement region is arbitrarily changed.
[0241] (composition)
[0242] The cobalt content in the first region R1 is preferably 50% by mass or more. As a result, it becomes easy to form a spinel structure in the first region R1. As a result, the first region R1 can have more spinel structures, thereby enabling the solid oxide fuel cell to have better conductivity. The lower limit of the cobalt content in the first region R1 is more preferably 55% by mass or more and 60% by mass or more. The upper limit of the cobalt content in the first region R1 is preferably 90% by mass or less, 80% by mass or less, and 75% by mass or less. The cobalt content in the first region R1 is preferably 50% by mass or more and 90% by mass or less, 55% by mass or more and 80% by mass or less, and 60% by mass or more and 75% by mass or less.
[0243] The lower limit of the nickel content in the first region R1 is preferably 0 mass % or more, 2 mass % or more, or 5 mass % or more. The upper limit of the nickel content in the first region R1 is preferably 10 mass % or less, 8 mass % or less, or 7 mass % or less. The nickel content in the first region R1 is preferably 0 mass % or more and 10 mass % or less, 2 mass % or more and 8 mass % or less, or 5 mass % or more and 7 mass % or less.
[0244] The lower limit of the oxygen content in the first region R1 is preferably 10% by mass or more, 20% by mass or more, or 30% by mass or more. The upper limit of the oxygen content in the first region R1 is preferably 40% by mass or less, 38% by mass or less, or 36% by mass or less. The oxygen content in the first region R1 is preferably 10% by mass or more and 40% by mass or less, 20% by mass or more and 38% by mass or less, or 30% by mass or more and 36% by mass or less.
[0245] The first region R1 preferably contains nickel, cobalt, and oxygen in an amount of 90% by mass or more, 92% by mass or more, or 95% by mass or more in total. The first region R1 preferably contains nickel, cobalt, and oxygen in an amount of 100% by mass or less, 98% by mass or less, or 96% by mass or less in total. The first region R1 preferably contains nickel, cobalt, and oxygen in an amount of 90% by mass or more and 100% by mass or less, 92% by mass or more and 98% by mass or less, or 95% by mass or more and 96% by mass or less in total.
[0246] The content of each of nickel, cobalt and oxygen in the first region R1 can be obtained by the following method. That is, it can be obtained by analyzing the composition of the region (first region R1) on the outer surface side of the skeleton body 25 using an EDX device attached to a scanning electron microscope (SEM) (for example, SEM part: trade name "SUPRA35VP", manufactured by Carl Zeiss Microscopy, EDX part: trade name "octane super", manufactured by Ametek) for the cross-section of the skeleton cut perpendicular to the length direction of the skeleton body 25. It was confirmed that as long as the measurement is performed by the above method in the same skeleton body 25, there is no deviation in the measurement result even if the measurement area is arbitrarily changed.
[0247] <Second Area>
[0248] (Crystal Structure)
[0249] The second region R2 has a layered rock salt structure of more than 80% by volume. The thermal expansion coefficient of the oxide having a layered rock salt structure is close to the thermal expansion coefficient of the fuel cell unit 100. As a result, the thermal expansion coefficient of the porous current collector 20 can be suppressed to be low as a whole, so the difference in thermal expansion coefficient with the fuel cell unit 100 can be suppressed, and the fuel cell unit 100 can be suppressed from rupture. The second region R2 preferably has a layered rock salt structure of more than 81% by volume, more than 82% by volume, and more than 85% by volume. The second region R2 preferably has a layered rock salt structure of less than 100% by volume, less than 95% by volume, and less than 90% by volume.
[0250] (thickness)
[0251] The ratio of the thickness of the second region R2 to the thickness of the skeleton body 25 is preferably 10% or more and 90% or less. As a result, the thermal expansion coefficient of the porous current collector 20 can be suppressed lower as a whole, so the difference in thermal expansion coefficient with the fuel cell unit 100 can be suppressed, and the fuel cell unit 100 can be suppressed from rupture. The lower limit of the ratio of the thickness of the second region R2 to the thickness of the skeleton body 25 is preferably 10% or more, 15% or more, or 25% or more. The upper limit of the ratio of the thickness of the second region R2 to the thickness of the skeleton body 25 is preferably 90% or less, 80% or less, or 70% or less. The ratio of the thickness of the second region R2 to the thickness of the skeleton body 25 is preferably 10% or more and 90% or less, 15% or more and 80% or less, or 25% or more and 70% or less. The ratio of the thickness of the second region R2 to the thickness of the skeleton body 25 is calculated as a percentage of the value obtained by dividing the thickness of the second region R2 by the thickness of the skeleton body 25.
[0252] The thickness of the second region R2 is preferably 1 μm or more and 45 μm or less, 3 μm or more and 35 μm or less, or 5 μm or more and 25 μm or less. Thus, in the solid oxide fuel cell, the rupture of the fuel cell unit 100 can be further suppressed. In addition, the thickness of the second region R2 can be adjusted by appropriately changing the current density and time as electrolysis conditions in the second step of the method for manufacturing the porous current collector 20.
[0253] In the porous current collector 20 , the thickness of the second region R2 can be obtained by calculating the difference between the thickness of the skeleton body 25 and the thickness of the first region R1 .
[0254] (composition)
[0255] The cobalt content in the second region R2 is preferably less than 50% by mass. Thus, it becomes easy to form a layered rock salt type structure in the second region R2. As a result, the second region R2 can have more layered rock salt type structures, so in the solid oxide fuel cell, the rupture of the fuel cell unit 100 can be further suppressed. The lower limit of the cobalt content in the second region R2 is more preferably 10% by mass or more, 20% by mass or more, and 30% by mass or more. The upper limit of the cobalt content in the second region R2 is more preferably 45% by mass or less and 40% by mass or less. The cobalt content in the second region R2 is more preferably 10% by mass or more and less than 50% by mass, 20% by mass or more and 45% by mass or less, 30% by mass or more and 40% by mass or less.
[0256] The lower limit of the nickel content in the second region R2 is preferably 30% by mass or more, 35% by mass or more, or 40% by mass or more. The upper limit of the nickel content in the second region R2 is preferably 90% by mass or less, 80% by mass or less, or 70% by mass or less. The nickel content in the second region R2 is preferably 30% by mass or more and 90% by mass or less, 35% by mass or more and 80% by mass or less, or 40% by mass or more and 70% by mass or less.
[0257] The lower limit of the oxygen content in the second region R2 is preferably 10% by mass or more, 20% by mass or more, or 30% by mass or more. The upper limit of the oxygen content in the second region R2 is preferably 40% by mass or less, 38% by mass or less, or 36% by mass or less. The oxygen content in the second region R2 is preferably 10% by mass or more and 40% by mass or less, 20% by mass or more and 38% by mass or less, or 30% by mass or more and 36% by mass or less.
[0258] The second region R2 preferably contains a total of 90 mass% or more, 92 mass% or more, 94 mass% or more of nickel, cobalt and oxygen. The second region R2 preferably contains a total of 100 mass% or less, 98 mass% or less, 96 mass% or less of nickel, cobalt and oxygen. The second region R2 preferably contains a total of 90 mass% or more and 100 mass% or less, 92 mass% or more and 98 mass% or less, 94 mass% or more and 96 mass% or less of nickel, cobalt and oxygen.
[0259] The respective contents of nickel, cobalt and oxygen in the second region R2 are obtained by the following method. That is, the respective contents of nickel, cobalt and oxygen in the skeleton body 25 can be obtained by analyzing the composition in the region (second region R2) on the inner 23 side of the skeleton body 25 using an EDX device attached to a scanning electron microscope (SEM) (e.g., SEM part: trade name "SUPRA35VP", manufactured by Carl Zeiss Microscopy, EDX part: trade name "octane super", manufactured by Ametek) for the cross-section of the skeleton cut perpendicular to the length direction of the skeleton body 25 (electron microscope image). It was confirmed that as long as the measurement is performed in the same skeleton body 25 by the above method, there is no deviation in the measurement result even if the measurement area is arbitrarily changed.
[0260] <<Method for producing porous current collector>>
[0261] The porous current collector 20 of the present embodiment can be manufactured by, for example, the following method. First, a solid oxide fuel cell 150 having the porous body 10 of the present embodiment 1 is obtained. Then, the solid oxide fuel cell is operated under the conditions of an operating temperature of 700 to 900°C and an operating time of 20 to 500 hours. Thus, the porous current collector 20 of the present embodiment 3 can be obtained. That is, the porous current collector 20 has a second skeleton 21, the second skeleton 21 has a three-dimensional network structure, the second skeleton 21 is composed of a skeleton body 25 and a hollow interior 23 surrounded by the skeleton body 25, the skeleton body 25 is composed of a first region R1 and a second region R2, the first region R1 is located on the outer surface side of the skeleton body 25, the second region R2 is located on the interior 23 side of the skeleton body 25, the skeleton body 25 contains a total of more than 90% by mass of nickel, cobalt and oxygen, the first region R1 has a spinel structure of more than 80% by volume, the second region R2 has a layered rock salt structure of more than 80% by volume, and the thickness of the first region R1 is 10% or more and 90% or less relative to the thickness of the skeleton body 25.
[0262] [Embodiment 4: Solid Oxide Fuel Cell]
[0263] use Figure 6A solid oxide fuel cell according to one embodiment of the present invention will be described. Figure 6 2 is a schematic cross-sectional view showing a solid oxide fuel cell 250 according to one embodiment of the present invention. Figure 6 In the embodiment, the solid oxide fuel cell 250 has a porous current collector 210 for hydrogen electrode, a porous current collector 220 for air electrode and a cell 100 for fuel cell. The cell 100 for fuel cell is arranged between the porous current collector 210 for hydrogen electrode and the porous current collector 220 for air electrode. Here, the "porous current collector 210 for hydrogen electrode" refers to a porous current collector on the side where hydrogen is supplied in a fuel cell. The "porous current collector 220 for air electrode" refers to a porous current collector on the side where a gas (such as air) containing oxygen is supplied in a fuel cell. In the solid oxide fuel cell 250 of the present embodiment, the porous current collector 220 for air electrode includes the porous current collector 20 of the present embodiment 1. That is, the solid oxide fuel cell 250 of the present embodiment has the porous current collector 20 of the present embodiment 1. As a result, the rupture of the cell 100 for fuel cell is not likely to occur, and a solid oxide fuel cell with excellent output performance can be provided.
[0264] The fuel cell unit 100 can have an air electrode, a hydrogen electrode, an electrolyte layer disposed between the air electrode and the hydrogen electrode, and an intermediate layer (not shown) disposed between them to prevent the electrolyte layer and the air electrode from reacting. As the air electrode, for example, an oxide of LaSrCo (LSC) can be used. As the electrolyte layer, for example, an oxide of Zr doped with Y (YSZ) can be used. As the intermediate layer, for example, an oxide of Ce doped with Gd (GDC) can be used. As the hydrogen electrode, for example, a mixture of YSZ and NiO2 can be used.
[0265] exist Figure 6 In the embodiment, the solid oxide fuel cell 250 further comprises: a first connector 112 having a fuel flow channel 114; and a second connector 122 having an oxidant flow channel 124. The fuel flow channel 114 is a flow channel for supplying fuel (e.g., hydrogen) to the hydrogen electrode. The fuel flow channel 114 is disposed on the main surface of the first connector 112 that faces the porous current collector 210 for the hydrogen electrode. The oxidant flow channel 124 is a flow channel for supplying an oxidant (e.g., oxygen) to the air electrode. The oxidant flow channel 124 is disposed on the main surface of the second connector 122 that faces the porous current collector 220 for the air electrode.
[0266] <<Method for manufacturing a solid oxide fuel cell having a porous current collector>>
[0267] The solid oxide fuel cell 250 having the porous current collector 20 of the present embodiment can be manufactured by appropriately using a known method, except that the porous current collector 20 of the present embodiment 3 is used in the porous current collector 220 for the air electrode. Therefore, the method for manufacturing the solid oxide fuel cell 250 having the porous current collector 20 should not be particularly limited except that the porous current collector 20 is used.
[0268] Example
[0269] Hereinafter, the present invention will be described in detail based on examples, but the present invention is not limited to the following examples.
[0270] [Example 1]
[0271] <<Manufacturing of porous body>>
[0272] In Example 1, porous bodies of Sample Nos. 1 to 18 were produced as follows.
[0273] <First step>
[0274] First, a resin molded body formed of a polyurethane resin (foamed resin) is prepared, and then a conductive coating obtained by mixing 20% by mass of acetylene black (conductive particles) and 5% by mass of PVdF (binder) is applied to the surface of the resin molded body to obtain a conductive resin molded body.
[0275] <Second step>
[0276] Next, a first nickel-cobalt alloy electroplating was performed on the conductive resin molded body under the following bath composition and electrolytic conditions, thereby obtaining a first porous body precursor.
[0277] (Bath composition)
[0278] Salt (aqueous solution): Nickel sulfamate (contains 110 g / L nickel in the plating bath)
[0279] Cobalt sulfamate (cobalt is contained in the electroplating bath at the concentration [g / L] listed in Table 1)
[0280] Boric acid: 40g / L
[0281] pH: 5
[0282] (Electrolysis Conditions)
[0283] Temperature: 60℃
[0284] Current density: recorded in Table 1
[0285] Anode: Insoluble anode
[0286] Time: recorded in Table 1
[0287] <Third step>
[0288] Next, a second nickel-cobalt alloy electroplating was performed on the first porous body precursor under the following bath composition and electrolytic conditions, thereby obtaining a second porous body precursor.
[0289] (Bath composition)
[0290] Salt (aqueous solution): Nickel sulfamate (contains 110 g / L nickel in the plating bath)
[0291] Cobalt sulfamate (cobalt is contained in the electroplating bath at the concentration [g / L] listed in Table 1)
[0292] Boric acid: 40g / L
[0293] pH: 5
[0294] (Electrolysis Conditions)
[0295] Temperature: 60℃
[0296] Current density: recorded in Table 1
[0297] Anode: Insoluble anode
[0298] Time: recorded in Table 1
[0299] <Fourth step>
[0300] Next, the second porous body precursor was subjected to heat treatment in the atmosphere under the following heat treatment conditions, thereby obtaining a porous body.
[0301] (Heat treatment conditions)
[0302] Temperature: 600℃
[0303] Time: 10 minutes
[0304] In this way, porous bodies of sample numbers 1 to 18 were produced.
[0305] [Table 1]
[0306] Table 1
[0307]
[0308] [Table 2]
[0309] Table 2
[0310]
[0311] <<Evaluation of characteristics of porous body>>
[0312] <Composition of the main skeleton of the first skeleton>
[0313] For the porous bodies of Sample Nos. 1 to 18, the composition of the skeleton body of the first skeleton was determined by the method described in Embodiment 1. The obtained results are described in the columns “Ni [mass %]”, “Co [mass %]”, and “Total [mass %]” in Table 2, respectively.
[0314] <Thickness of the main frame of the first frame, thickness of the first layer, and thickness of the second layer>
[0315] For the porous bodies of sample numbers 1 to 18, the thickness of the skeleton body of the first skeleton was determined by the method described in Implementation Example 1. The obtained results are recorded in the "Thickness [μm]" column in the "Skeleton Body" column of Table 2. In addition, for the porous bodies of sample numbers 1 to 18, the thickness of the first layer was determined by the method described in Implementation Example 1. The obtained results are recorded in the "Thickness [μm]" column in the "First Layer" column of Table 2. In addition, for the porous bodies of sample numbers 1 to 18, the thickness of the second layer was determined by the method described in Implementation Example 1. The obtained results are recorded in the "Thickness [μm]" column in the "Second Layer" column of Table 2. In addition, the ratio of the thickness of the first layer to the thickness of the skeleton body of the first skeleton was determined by the method described in Implementation Example 1. The obtained results are recorded in the "Thickness Ratio [%]" column in the "First Layer" column of Table 2. In addition, the ratio of the thickness of the second layer to the thickness of the skeleton body of the first skeleton was determined by the method described in Implementation Example 1. The obtained results are described in the column “Thickness ratio [%]” in the column “Second layer” in Table 2.
[0316] <Cobalt content in the first layer and cobalt content in the second layer>
[0317] For the porous bodies of sample numbers 1 to 18, the cobalt content in the first layer was determined by the method described in Embodiment 1. The obtained results are recorded in the "Co content [mass %]" column in the "First layer" column of Table 2. In addition, for the porous bodies of sample numbers 1 to 18, the cobalt content in the second layer was determined by the method described in Embodiment 1. The obtained results are recorded in the "Co content [mass %]" column in the "Second layer" column of Table 2.
[0318] [Example 2]
[0319] <<Manufacturing of porous current collector>>
[0320] In Example 2, porous current collectors of sample numbers 101 to 118 were produced as follows.
[0321] First, a solid oxide fuel cell having a porous body of sample numbers 1 to 18 (porous body for air electrode), a Ni mesh made by Nilaco Co., Ltd. (porous body for hydrogen electrode), a unit "YSZ unit" (trademark) made by Elcogen Co., Ltd., and a connector were used. Then, the solid oxide fuel cell was operated under the conditions of an operating temperature of 730° C. and an operating time of 24 hours, thereby producing a solid oxide fuel cell having a porous current collector of sample numbers 101 to 118.
[0322] <<Evaluation of characteristics of porous current collector>>
[0323] <Composition of the main skeleton of the second skeleton>
[0324] For the porous current collectors of sample numbers 101 to 118, the composition of the skeleton body of the second skeleton was determined by the method described in Embodiment 3. The obtained results are respectively recorded in the "Ni [mass %]" column of Table 3, the "Co [mass %]" column of Table 3, the "O [mass %]" column of Table 3, and the "Total [mass %]" column of Table 3.
[0325] <Cobalt Content in First Region R1 and Cobalt Content in Second Region R2>
[0326] For the porous current collectors of sample numbers 101 to 118, the cobalt content in the first region R1 was determined by the method described in Embodiment 3. The obtained results are recorded in the "Co content [mass %]" column in the "First region R1" column of Table 4. In addition, for the porous current collectors of sample numbers 101 to 118, the cobalt content in the second region R2 was determined by the method described in Embodiment 3. The obtained results are recorded in the "Co content [mass %]" column in the "Second region R2" column of Table 4.
[0327] <Thickness of the frame body of the second frame, thickness of the first region R1, and thickness of the second region R2>
[0328] For the porous current collectors of sample numbers 101 to 118, the thickness of the skeleton body of the second skeleton was obtained by the method described in Implementation Example 3. The obtained results are recorded in the "Thickness [μm]" column in the "Skeleton Body" column of Table 3. In addition, for the porous current collectors of sample numbers 101 to 118, the thickness of the first region R1 was obtained by the method described in Implementation Example 3. The obtained results are recorded in the "Thickness [μm]" column in the "First Region R1" column of Table 4. In addition, for the porous current collectors of sample numbers 101 to 118, the thickness of the second region R2 was obtained by the method described in Implementation Example 3. The obtained results are recorded in the "Thickness [μm]" column in the "Second Region R2" column of Table 4. In addition, for the porous current collectors of sample numbers 101 to 118, the ratio of the thickness of the first region R1 to the thickness of the skeleton body was obtained by the method described in Implementation Example 3. The obtained results are recorded in the "Thickness Ratio [%]" column in the "First Region R1" column of Table 4. In addition, for the porous current collectors of sample numbers 101 to 118, the ratio of the thickness of the second region R2 to the thickness of the skeleton body was determined by the method described in Embodiment 3. The obtained results are recorded in the "Thickness ratio [%]" column in the "Second region R2" column of Table 4.
[0329] <Ratio of the spinel structure in the first region R1 and ratio of the layered rock salt structure in the second region R2>
[0330] For the porous current collectors of sample numbers 101 to 118, the proportion of the spinel structure in the first region R1 was determined by the method described in Implementation Example 3. The results obtained are recorded in the "Proportion of spinel structure [volume %]" column in the "First region R1" column of Table 4. In addition, for the porous current collectors of sample numbers 101 to 118, the proportion of the layered rock salt type structure in the second region R2 was determined by the method described in Implementation Example 3. The results obtained are recorded in the "Proportion of layered rock salt type structure [volume %]" column in the "Second region R2" column of Table 4.
[0331] <Conductivity of porous current collector>
[0332] The area resistivity of the porous current collectors of Sample Nos. 101 to 118 was measured by the following method to evaluate the conductivity of each porous current collector. A low area resistivity of the porous current collector means that the conductivity of the porous current collector is high.
[0333] The porous current collector is sandwiched by two interconnect simulation plates 202 from both the first main surface side and the second main surface side of the porous current collector. Figure 7), the two interconnect simulation plates 202 are connected to a resistance measuring machine 200 (manufactured by Tsuruga Electric Co., Ltd., trademark: low resistance meter 356E) via a platinum wire 201 for conducting electricity. Next, after the interconnect simulation plate 202 and the porous current collector are heated to 800°C in a constant temperature bath, the area resistivity is measured using a four-terminal method. The results are recorded in Table 5, respectively, in the "Area resistivity [mΩ·cm 2 ]” column.
[0334] The porous current collectors of sample numbers 103 to 106, 109, 111, 113, 115 to 118 correspond to the examples. On the other hand, the porous current collectors of sample numbers 101, 102, 107, 108, 110, 112, and 114 correspond to the comparative examples. The porous current collectors of sample numbers 103 to 106, 109, 111, 113, 115 to 118 have significantly better electrical conductivity than the porous current collectors of sample numbers 107, 108, 110, and 112 in the comparative examples. In addition, the high electrical conductivity of the porous current collector means that the output performance of the solid oxide fuel cell having the porous current collector is high. Therefore, "the porous current collectors of sample numbers 103 to 106, 109, 111, 113, 115 to 118 have exceptionally excellent conductivity compared to the porous current collectors of sample numbers 107, 108, 110, and 112 in the comparative examples" means "the solid oxide fuel cell having the porous current collectors of sample numbers 103 to 106, 109, 111, 113, 115 to 118 has exceptionally excellent output performance compared to the solid oxide fuel cell having the porous current collectors of sample numbers 107, 108, 110, and 112 in the comparative examples."
[0335] <Thermal shock test>
[0336] The solid oxide fuel cells with porous current collectors of sample numbers 101 to 118 for the evaluation of "conductivity of porous current collectors" were kept at 700°C for 200 hours. Then, the temperature was raised and lowered in the range of 100°C to 700°C for 30 times. Next, the output performance [mW / cm 2 ] and the presence or absence of cell rupture. In addition, the output performance of the solid oxide fuel cell [mW / cm 2 ], by measuring the current density between 0 and 500 mA / cm 2 The maximum output when the change occurs is obtained. The obtained output performance [mW / cm 2 The results are recorded in Table 5, “Output performance [mW / cm 2 ]” column. In addition, the evaluation results of the presence or absence of cell rupture are recorded in the “Presence or absence of cell rupture” column of Table 5. In addition, “Output performance [mW / cm2 The “-” in the “Output performance [mW / cm 2 The reason for “unable to measure” is recorded in parentheses in the “]” column.
[0337] The porous current collectors of sample numbers 103 to 106, 109, 111, 113, 115 to 118 showed an exceptionally excellent cell crack suppression effect in solid oxide fuel cells compared to the porous current collectors of sample numbers 101, 102, and 114. In addition, the porous current collectors of sample numbers 103 to 106, 109, 111, 113, 115 to 118 showed excellent output performance even in a thermal shock test (i.e., under severe conditions).
[0338] [Table 3]
[0339] Table 3
[0340]
[0341] [Table 4]
[0342] Table 4
[0343]
[0344] [Table 5]
[0345] Table 5
[0346]
[0347] It can be seen that the porous current collectors of sample numbers 103 to 106, 109, 111, 113, 115 to 118 suppress the rupture of the fuel cell unit in the solid oxide fuel cell and have excellent conductivity. In addition, it can be seen that the solid oxide fuel cell having the porous current collectors of sample numbers 103 to 106, 109, 111, 113, 115 to 118 is not prone to rupture of the fuel cell unit and has excellent output performance.
[0348] Although the embodiments and examples of the present invention have been described above, it is intended from the outset that the configurations of the above-described embodiments and examples be appropriately combined.
[0349] The embodiments disclosed this time should be considered as illustrative in all aspects and not restrictive. The scope of the present invention is indicated by the claims rather than the above-described embodiments, and is intended to include all modifications within the meaning and scope equivalent to the claims.
[0350] Description of Reference Numerals
[0351] 10: porous body; 11: first skeleton; 12: first layer; 13: interior; 14: pores; 15: skeleton body; 16: second layer; 20: porous current collector; 21: second skeleton; 23: interior; 24: pores; 25: skeleton body; 100: unit for fuel cell; 110: porous body for hydrogen electrode; 112: first connector; 114: fuel flow channel; 120: porous body for air electrode; 122: second connector; 124: oxidant flow channel; 150: solid oxide fuel cell with porous body; 200: resistance measuring machine; 201: platinum wire; 202: connector simulation board; 210: porous current collector for hydrogen electrode; 220: porous current collector for air electrode; 250: solid oxide fuel cell with porous current collector; R1: first region; R2: second region.
Claims
1. A porous body having a first skeleton, wherein the first skeleton has a three-dimensional network structure, The first frame is composed of a frame body and a hollow interior surrounded by the frame body. The skeleton body is composed of a first layer and a second layer. The first layer is located on the outer surface side of the skeleton body, The second layer is located on the inner side of the skeleton body, The skeleton body contains nickel and cobalt in total of 70 mass % or more, The cobalt content in the first layer is 50 mass % or more, The cobalt content in the second layer is less than 50% by mass. A ratio of the thickness of the first layer to the thickness of the skeleton body is 10% or more and 90% or less.
2. A solid oxide fuel cell comprising the porous body according to claim 1.
3. A porous current collector having a second skeleton, wherein the second skeleton has a three-dimensional network structure, The second frame is composed of a frame body and a hollow interior surrounded by the frame body. The skeleton body is composed of a first region and a second region. The first region is located on the outer surface side of the skeleton body, The second region is located on the inner side of the skeleton body, The skeleton body contains nickel, cobalt and oxygen in total of 90 mass % or more, The first region has a spinel structure of 80% by volume or more, The second region has a layered rock salt structure of 80% or more by volume, A ratio of the thickness of the first region to the thickness of the skeleton body is 10% or more and 90% or less.
4. The porous current collector according to claim 3, wherein: The cobalt content in the first region is 50 mass % or more, The cobalt content in the second region is less than 50 mass %.
5. A solid oxide fuel cell comprising the porous current collector according to claim 3 or 4.
Citation Information
Patent Citations
Air electrode current collector for solid oxide fuel cells and solid oxide fuel cells containing the same
JP2017507452A
Image forming apparatus and control method for the same
JP2022155330A